Sistem Pakar Untuk Diagnosa Penyakit Sapi Menggunakan Metode Bayes - Putri Eka Wardani; Yessica Siagian; MHD Ihsan (Forum Kerjasama Pendidikan Tinggi, 2022)
Cow disease can attack animals, both young and adult, in this case it is necessary to do a quick diagnosis to provide basic knowledge about cow disease. Advances in expert systems can overcome this problem, namely by designing a web-based computer system that is integrated with databases and programming languages ​​such as PHP-MySQL so that it can help farmers to diagnose cattle disease. The purpose of this research is to build an expert system for diagnosing cow disease based on web. The application of the expert system in this decision making uses the Bayes method, in probability theory and statistics, the Bayes theorem is a theorem with two different interpretations. In Bayes' interpretation, this theorem states that one of the decision-making methods, this method was developed to solve decision-making problems by determining the probability value of the event and the value of evidence obtained from the facts about the object under study. What kind of cow did he experience in order to get a solution with treatment. From the results of testing and implementation of this expert system, it has been able to produce Brucellosis (Transmitted Keluron) disease with a weight = 2 which is higher than the weight of other cattle diseases